International Journal of Health Economics and Management - David, Guy.; Barros, Pedro Pita.; Dranove, David; Pauly, Mark.; Bundorf, M. Kate.; Dormont, Brigitte; Howard, David; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The focus of the International Journal of Health Economics and Management is on health care systems and on the behavior of consumers, patients, and providers of such services. The links among management, public policy, payment, and performance are core topics of the relaunched journal. The demand for health care and its cost remain central concerns. Even as medical innovation allows providers to improve the lives of their patients, questions remain about how to efficiently deliver health care services, how to pay for it, and who should pay for it. These are central questions facing innovators, providers, and payers in the public and private sectors. One key to answering these questions is to understand how people choose among alternative arrangements, either in markets or through the political process. The choices made by healthcare managers concerning the organization and production of that care are also crucial. There is an important connection between the management of a health care system and its economic performance. The primary audience for this journal will be health economists and researchers in health management, along with the larger group of health services researchers. In addition, research and policy analysis reported in the journal should be of interest to health care providers, managers and policymakers, who need to know about the pressures facing insurers and governments, with consequences for regulation and mandates. The editors of the journal encourage submissions that analyze the behavior and interaction of the actors in health care, viz. consumers, providers, insurers, and governments. Preference will be given to contributions that combine theoretical with empirical work, evaluate conflicting findings, present new information, or compare experiences between countries and jurisdictions. In addition to conventional research articles, the journal will include specific subsections for shorter concise research findings and contributions to management and policy that provide important descriptive data or arguments about what policies follow from research findings. The composition of the editorial board is designed to cover the range of interest among economics and management researchers. Officially cited as: Int J Health Econ Manag From 2001 to 2014 the journal was published as International Journal of Health Care Finance and Economics. (Articles published in Vol. 1-14 officially cited as: Int J Health Care Finance Econ).
Keywords: Health care management; Health services administration; Public health; Health administration; Public finance; Economic policy; Health economics; Medical economics; Public Health; Health Economics; Health Care Management; Health Administration; Public Finance; Economic Policy